Effect of the Initial Support of the Tunnel on the Characteristics of Rockburst: Case Study and Mechanism Analysis - Chunchi Ma; Junqi Fan; Xiang Ji; Xiaoyan Shi; Jun Zeng (Advances in Civil Engineering)
Rockburst is still a stubborn disease in the field of engineering geology. The present research pays more attention to the influence of geological conditions on rockburst and less to the influence of type and stiffness of engineering support on rockburst. We explore the influence of support stiffness from weak to strong on rockburst and reveal the characteristics of fracture and microseismicity during rockburst through microseismic monitoring and numerical simulation. The main results and conclusions can be drawn: (1) Strong stiffness support makes the surrounding rock accumulates higher energy before rockburst. The evolution of microseismicity and its indexes can be used as precursors of potentially strong rockburst. (2) Strong stiffness support is easy to concentrate high stress under the action of surrounding rock pressure, and it is easy to fail under the disturbance of external load. This will produce a “sudden unloading effect” on the surrounding rock mass and may lead to a more serious rockburst. Numerical simulation verifies the existence of that effect and are consistent with the actual signs of failure. Our research is helpful to clarify the rockburst problem in the field of engineering geology, specifically to reveal the mechanism of rockburst and the early warning criteria of rockburst hazard under the action of supporting structure, which can provide practical data and theoretical support for scientific and reasonable prevention and control of rockburst risk in tunnel and underground engineering.